2019
DOI: 10.18203/2394-6040.ijcmph20193451
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cyclosporine 0.05% in patients with dry eye syndrome

Abstract: Background: An even and smooth ocular surface is vital for the functioning and comfort of the eyes. Dry eye is a group of disorders of the tear film which is due to either decreased production or increased evaporation and is associated with symptoms of ocular discomfort. Smoking and drugs have been suggested as risk factors in various studies. Cyclosporine has been shown to reduce the cell-mediated inflammatory reactions associated with the inflammatory ocular surface disease.Methods: 50 eyes of 25 patients su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similar finding in a study by Henry D. Perry et al 4 where mean age was observed to be 57 years in patients with mild dry eyes and 66 years in patients with moderate dry eyes and 68 years in severe cases. Mean age of the patients was 44.2 years in a study by Jitender Phogat et al 8 and 47 years in a study by Tageldin M. Othman et al, 9 So we can say by this pattern that probability of dry eye disease increases after 40 years of age.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Similar finding in a study by Henry D. Perry et al 4 where mean age was observed to be 57 years in patients with mild dry eyes and 66 years in patients with moderate dry eyes and 68 years in severe cases. Mean age of the patients was 44.2 years in a study by Jitender Phogat et al 8 and 47 years in a study by Tageldin M. Othman et al, 9 So we can say by this pattern that probability of dry eye disease increases after 40 years of age.…”
Section: Discussionmentioning
confidence: 86%
“…Mean OSDI score in a study by Pinnita Prabhasawat et al 12 was 43.32. In a study by Jitender Phogat et al 8 the score of ocular symptoms before the beginning of the treatment was 2.25±0.41 and this score improved after 4 weeks to 1.36±0.14, to 1.11±0.18 after 8 weeks, and to 0.6±0.44 after 12 weeks with a statistically significant difference (p=0.01).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations